Tocilizumab Treatment of Patients with Systemic Sclerosis: Clinical Data. (2017) - Khanna, Dinesh; Jahreis, Angelika; Furst, Daniel E.
Systemic sclerosis (SSc) is an immune-mediated disease characterized by progressive, and often severe, inflammation and fibrosis of the skin and internal organs, such as the lungs, heart, kidneys, and gastrointestinal tract. There is an unmet medical need to treat patients with SSc given the high SSc-related mortality rate. Furthermore, disease-modifying therapies are lacking, and current treatment options focus on the management of individual organ-specific complications associated with the disease. Immunosuppressive therapies are the mainstay of pharmacologic management of major SSc-associated complications, such as skin and lung manifestations, but their overall effectiveness is limited and toxicity issues are common. Advances in understanding of the pathological processes involved in the immunologic and fibrotic mechanisms of SSc have led to clinical research focusing on targeted immunotherapies, in an effort to develop much needed disease-modifying treatment options. The interleukin-6 receptor-alpha antagonist tocilizumab has demonstrated promising efficacy in a phase 2 trial and is being investigated in a phase 3 trial. This article provides an overview of current pharmacologic treatment options for the management of SSc-related complications and discusses tocilizumab for the treatment of SSc in clinical trials.